Synthesis, characterization and antibacterial activity of (E)-chalcone derivatives - Abdula, Ahmed Mutanabbi (European Journal of Chemistry, 2013)
(E)-Chalcone derivatives were synthesized by the Claisen-Schmidt condensation of aromatic aldehydes with methyl ketones. 5-Arylfuran-2-carboxaldehydes (1a-b) were synthesized by Meerwein´s method and condensed with 2-acetylpyrole or 2-acetylfuran to produce the new chalcone derivatives (2a-d). The new chalcones were characterized using FT-IR and GC-MS. The synthesized compounds were also screened against some bacterial species to evaluate their activity as promising antibacterial agents.